Calculating reduced electric field in diffusion regime of DC discharge positive column - Lisovskiy, V.A.; Artushenko, E.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2015)
The present paper outlines an analytical model of the positive column of the direct current discharge in a diffusion mode. We consider the case when charged particles are produced through direct ionization of gas molecules via electron impact and the ambipolar escape of them to discharge tube walls is the sole mechanism of their loss. We solved the equation for the charged particles balance and obtained simple formulas for the reduced electric field E/p in the positive column in molecular gases. Results of our calculations for E/p values in nitrogen are in good agreement with experimental and theoretical data of other authors for low discharge current values. Представлена аналитическая модель положительного столба разряда постоянного тока в диффузионном режиме. Рассмотрен случай, в котором заряженные частицы образуются вследствие прямой ионизации молекул газа электронным ударом, а единственным механизмом потерь является их амбиполярный уход на стенки разрядной трубки. Решено уравнение баланса заряженных частиц и получены простые формулы для приведенного электрического поля E/p в положительном столбе в молекулярных газах. Результаты наших расчетов для E/p в азоте хорошо согласуются с экспериментальными и теоретическими данными других авторов для случая низких разрядных токов. Представлено аналітичну модель позитивного стовпа розряду постійного струму в дифузійному режимі. Розглянуто випадок, коли заряджені частинки утворюються внаслідок прямої іонізації молекул газу електронним ударом, а єдиним механізмом втрат є їх амбіполярний вихід на стінки розрядної трубки. Розв’язано рівняння балансу заряджених частинок і отримані прості формули для зведеного електричного поля E/p у позитивному стовпі в молекулярних газах. Результати наших розрахунків для E/p в азоті добре узгоджуються з експериментальними і теоретичними даними інших авторів для випадку низьких розрядних струмів.